Self-care of people with intestinal ostomy: beyond the procedural towards rehabilitation - Vanessa Damiana Menis Sasaki; André Aparecido da Silva Teles; Natália Michelato Silva; Tatiana Mara da Silva Russo; Lorena Alves Pantoni; Janderson Cleiton Aguiar; Helena Megumi Sonobe
ABSTRACT Objectives: to interpret the self-care experience of people with intestinal ostomy registered in an ostomy program, based on the framework of the Social Model of Disability. Methods: qualitative exploratory research, with the participation of nine people with intestinal ostomy, based on the Social Model of Disability. Results: majority were elderly, married, male with colostomy due to colorectal neoplasia. The self-care of these people was analyzed in two thematic groups: "Interdisciplinary assistance needed for people with intestinal ostomy" and "Self-care for the rehabilitation of the person with intestinal ostomy". It was proved that there was a need for a specialized health team, offering information on disabilities, teaching self-care and perioperative follow-up. Final Considerations: when the social barriers of physical disabilities are overcome in the context of assistance for health and life, self-care will go beyond the reductionist vision of procedural care, towards comprehensive care, favoring the achievement of rehabilitation and the quality of survival.